Factors Related to Nutritional Status in Grade 4 and 5 Students at SDN Jatimekar 01 Bekasi in 2024 - Kurniawan, Slamet Santoso; Putri, Ananda Kamilah (LPPM Universitas Mohammad Husni Thamrin, 2025)
Nutritional status is a body condition that is influenced by the intake and release of nutrients from the food and drinks that have been consumed. Can guarantee the quality of activities carried out and meet the body's nutritional needs. If food intake and body expenditure are balanced then the body is considered to be in a normal nutritional condition. The aim of this research is to determine factors related to nutritional status in grade 4 and 5 students at SDN Jatimekar 01 2025. This research is quantitative using a cross sectional design. The population in this study were all students in grades 4 and 5 at SDN Jatimekar 01, totaling 131 respondents and a sample of 125 respondents. Total random sampling technique. The research instruments used were digital scales, microtoise, breakfast habits questionnaire, food recall formular, snack habits questionnaire and FFQ sheet for fast food. The analysis used was univariate and bivariate using the chi-square test. The results showed that 7 students (5.6%) experienced malnutrition, 46 students (36.8%) experienced good nutrition, and 72 students (57.6%) experienced overnutrition. There is a significant relationship between energy intake (p-value 0.000), fat intake (p-value 0.000), carbohydrate intake (p-value 0.000), snack habits (p-value 0.016), and fast food consumption (p-value 0.014) on the nutritional status of elementary school children and there was no significant relationship, namely breakfast habits (p-value 0.135). It is hoped that respondents will reduce the frequency of consuming fast food such as instant noodles, fried chicken, french fries and advise the school to pay attention to students' nutritional status by measuring nutritional status every semester to see the students' health condition.